2018
DOI: 10.1017/s1092852918001062
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal underpinnings of cognitive impairment and - improvement in mood disorders

Abstract: Neuropsychiatric illnesses including mood disorders are accompanied by cognitive impairment, which impairs work capacity and quality of life. However, there is a lack of treatment options that would lead to solid and lasting improvement of cognition. This is partially due to the absence of valid and reliable neurocircuitry-based biomarkers for pro-cognitive effects. This systematic review therefore examined the most consistent neural underpinnings of cognitive impairment and cognitive improvement in unipolar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 131 publications
(375 reference statements)
3
57
0
Order By: Relevance
“…In a recent systematic review of functional magnetic resonance imaging (fMRI) studies of cognitiveimpairment and -improvement across mood disorders, we identified some promising neurocircuitry-based targets for future cognition treatments. 19 Abnormal (hypo-and hyper-) activation of the dorsal prefrontal cortex (PFC) and failure to suppress the default mode network (DMN) were consistently observed across mood disorders and cognitive domains 19 (Figures 1 and 2). This finding is similar to that of a previous review article in depression by Fossati.…”
Section: Common Neural Correlates For Cognitive Impairments and Improvements Across Mood Disordersmentioning
confidence: 99%
“…In a recent systematic review of functional magnetic resonance imaging (fMRI) studies of cognitiveimpairment and -improvement across mood disorders, we identified some promising neurocircuitry-based targets for future cognition treatments. 19 Abnormal (hypo-and hyper-) activation of the dorsal prefrontal cortex (PFC) and failure to suppress the default mode network (DMN) were consistently observed across mood disorders and cognitive domains 19 (Figures 1 and 2). This finding is similar to that of a previous review article in depression by Fossati.…”
Section: Common Neural Correlates For Cognitive Impairments and Improvements Across Mood Disordersmentioning
confidence: 99%
“…8 ), but systematic analyses of their incidence, life-progression and causal link with treatment are not yet available. It is likely that the aberrant function of cortico-thalamo-cortical networks (underlying the generation of SWD and absence seizures) ( Crunelli and Leresche, 2002 a ; Blumenfeld, 2005 a ) combines with the abnormal activity of basal ganglia-limbic-monoamine networks (underlying attention deficits, cognitive impairments and mood disorders) ( De Deurwaerdère et al , 2017 ; Miskowiak and Petersen, 2019 ; Park et al , 2019 ) to generate the overall neuropsychiatric comorbid phenotype of absence seizure ( Fig. 8 , left).…”
Section: Introductionmentioning
confidence: 99%
“…Important information is maintained, while non-relevant stimuli must be suppressed or ignored. Dysfunctions of cognitive control (CC) processes are at the core of many psychopathological conditions [1,2], comprise the intentional selection of thoughts, emotions, and behaviours based on current task demands [3] involving functions of attention, memory, and emotional control [4], and are associated with altered patterns of brain activation [5,6]. The prefrontal cortex (PFC), particularly the dorsolateral prefrontal cortex (dlPFC), is known to be highly involved in CC processes [7] by means of processes related to working memory [8], encoding of task relevant rules and responses [9], and emotion regulation [10].…”
Section: Introductionmentioning
confidence: 99%